(untitled) (Research, Society and Development, 2022)
The number of drug users, whether legal or illegal, natural, semi-synthetic or synthetic, is increasing every day around the world, and proving to be a serious problem for public health, since they cause damage to health general and oral health of the individual, as well as psychological, economic and social damages, both for the users and for their families. This work aims to develop an informational cluster about the damage caused to the oral cavity due to the use of drugs, whether legal or illegal, natural, semi-synthetic or synthetic, which will serve as a source of information for dental students and professionals in the area. A descriptive narrative literature review was carried out, with informations to academics and dentistry professionals in the health area, using scientific articles available in online databases such as BVSalud, PUBMed, SciELO and Google Scholar as a bibliographic basis, all articles are presented in Portuguese. At the end of this work, it was concluded how necessary it is to create education programs within the faculties of dentistry, to prepare academics to perform the care of drug users.